Soil Property and Class Maps of the Conterminous United States at 100‐Meter Spatial Resolution. Issue 1 (12th January 2018) - Ramcharan, Amanda; Hengl, Tomislav; Nauman, Travis; Brungard, Colby; Waltman, Sharon; Wills, Skye; Thompson, James
Abstract : Core Ideas: Ensemble machine learning methods were used to obtain gridded soil property and class maps. Final predictions were generated for six soil properties and two soil classes at 100‐m resolution. Soil data are easier to integrate with spatially explicit models compared with multicomponent map units. Soil property maps are available at seven standard depths. With growing concern for the depletion of soil resources, conventional soil maps need to be updated and provided at finer and finer resolutions to be able to support spatially explicit human–landscape models. Three US soil point datasets—the National Cooperative Soil Survey Characterization Database, the National Soil Information System, and the Rapid Carbon Assessment dataset—were combined with a stack of over 200 environmental datasets and gSSURGO polygon maps to generate complete coverage gridded predictions at 100‐m spatial resolution of six soil properties (percentage of organic C, total N, bulk density, pH, and percentage of sand and clay) and two US soil taxonomic classes (291 great groups [GGs] and 78 modified particle size classes [mPSCs]) for the conterminous United States. Models were built using parallelized random forest and gradient boosting algorithms as implemented in the ranger and xgboost packages for R. Soil property predictions were generated at seven standard soil depths (0, 5, 15, 30, 60, 100, and 200 cm). Prediction probability maps for US soil taxonomic classifications were also generated. Cross validation results indicated an out‐of‐bag classification accuracy of 60% for GGs and 66% for mPSCs; for soil properties, RMSE for leave‐location‐out cross‐validation was 0.74 ( R 2 = 0.68), 17.8 wt% ( R 2 = 0.57), 12 wt% ( R 2 = 0.46), 3.63 wt% ( R 2 = 0.41), 0.2 g cm −3 ( R 2 = 0.42), and 0.27 wt% ( R 2 = 0.39) for pH, percent sand and clay, weight percentage of organic C, bulk density, and weight percentage of total N, respectively. Nine independent validation datasets were used to assess prediction accuracies for soil class models, and results ranged between 24 and 58% and between 24 and 93% for GG and mPSC prediction accuracies, respectively. Although mapping accuracies were variable and likely lower than gSSURGO in some areas, this modeling approach can enable easier integration of soil information with spatially explicit models compared with multicomponent map units.